Half in Shadow The Life and Legacy of Nellie Y. McKay - Benjamin, Shanna Greene (The University of North Carolina Press, 2021)
Nellie Y. McKay (1930-2006) was a pivotal figure in contemporary American letters. The author of several books, McKay is best known for coediting the canon-making with Henry Louis Gates Jr., which helped secure a place for the scholarly study of Black writing that had been ignored by white academia. However, there is more to McKay's life and legacy than her literary scholarship. After her passing, new details about McKay's life emerged, surprising everyone who knew her. Why did McKay choose to hide so many details of her past? Shanna Greene Benjamin examines McKay's path through the professoriate to learn about the strategies, sacrifices, and successes of contemporary Black women in the American academy. Benjamin shows that McKay's secrecy was a necessary tactic that a Black, working-class woman had to employ to succeed in the white-dominated space of the American English department. Using extensive archives and personal correspondence, Benjamin brings together McKay's private life and public work to expand how we think about Black literary history and the place of Black women in American culture.